Innovation and Dynamism. Interaction between Systems and Technical Progress - Kornai, János (Journal of Public Governance, 2010)
In his essay, the great Hungarian economist János Kornai compares the level of innovativeness of capitalism and socialism. In Kornai’s opinion, no comprehensive studies have been made so far on interactions between a system change and changes in our way of thinking on creating and using new products and new technologies. Kornai uses the term ‘technological progress’ in a much wider sense, as a very general phenomenon, a part of modernization, bringing profound changes to our everyday lives. In his analysis of the notions of the innovation process, invention, innovation and diffusion, the author refers to Joseph Schumpeter’s approach toward the nature of capitalism, and argues that only the capitalist system is fully capable of benefitting from the opportunities of development offered by the innovation process, which has made capitalism the most dynamic system of all. A rapid increase of innovativeness and dynamism is not a random phenomenon, but a deeply rooted system-specific property of capitalism. The inability of the socialist system to create groundbreaking new products, and its general technological backwardness are also a deeply rooted system-specific property.